2021
DOI: 10.1177/1932296821996434
|View full text |Cite
|
Sign up to set email alerts
|

Small Fiber Neuropathy in Diabetes Polyneuropathy: Is It Time to Change?

Abstract: Diabetes polyneuropathy is an important complication of diabetes polyneuropathy, and its notable sequelae of foot ulceration, autonomic dysfunction, and neuropathic pain are associated with significant morbidity and mortality. Despite the major impact on quality of life and health economic costs, it remains underdiagnosed until late in its natural history, and there is lack of any intervention that can reverse its clinical progress. Assessment of small fiber neuropathy (SFN) in diabetes offers an opportunity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 78 publications
0
18
0
1
Order By: Relevance
“…La polineuropatía es una complicación grave de la diabetes mellitus que deriva en úlceras tórpidas, disautonomía y dolor de intensidad grave. Se relaciona con un aumento de la morbimortalidad 40 . La detección de NFF permite de una manera precoz detectar las primeras complicaciones de la diabetes y tomar medidas terapéuticas que frenen o reviertan esta situación.…”
Section: Diabetes Mellitus Como Paradigma De La Nffunclassified
“…La polineuropatía es una complicación grave de la diabetes mellitus que deriva en úlceras tórpidas, disautonomía y dolor de intensidad grave. Se relaciona con un aumento de la morbimortalidad 40 . La detección de NFF permite de una manera precoz detectar las primeras complicaciones de la diabetes y tomar medidas terapéuticas que frenen o reviertan esta situación.…”
Section: Diabetes Mellitus Como Paradigma De La Nffunclassified
“…Instead, pinprick and temperature sensation are recommended for assessment of small nerve fiber function. However, sudomotor dysfunction is a critical pathophysiological process in the pathogenesis of diabetes-related foot disease, especially in the early stages [63][64][65]. Research suggests that evaluation of sudomotor function helps identify individuals at risk for foot ulceration [66,67], but whether such evaluation should be conducted routinely is unclear.…”
Section: Yearmentioning
confidence: 99%
“…Research suggests that evaluation of sudomotor function helps identify individuals at risk for foot ulceration [66,67], but whether such evaluation should be conducted routinely is unclear. Neuropad is an accurate, sensitive, and cost-effective point-of-care test that is used to evaluate sudomotor function [65,[68][69][70][71]. Since Neuropad has high sensitivity and negative predictive value for detecting small nerve fiber dysfunction [72,73], it may be used as an adjunct clinical test during diabetic foot screening.…”
Section: Yearmentioning
confidence: 99%
“…In our initial proof‐of‐concept study, we found a difference between groups of people with T1DM with and without DPN and theorized that the groups could be distinguished at an earlier point during the examination. Also, we previously only evaluated the intensity of the flare response without assessing the flare area size, which is important for a direct comparison to established methods 7 . Therefore, the present study aimed to (1) compare the FLPI‐assessed, quantitative measures of mean flare intensity with a measurement of flare area size, (2) evaluate how long each method needs to distinguish people with T1DM and established DPN from people with T1DM without DPN, and (3) evaluate the diagnostic performance of the two methods compared to established measures (CCM and quantitative sensory testing [QST]).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The latter is a method to evaluate small nerve fiber function through a provoked flare response assessed using either laser-Doppler imaging flare (LDI FLARE ) or full-field laser speckle perfusion imaging (FLPI) following approximately 30 min of local heating. 6,7 The technique provides a non-invasive assessment of C-fiber function and show strong correlations with structural measures like CCM and intraepidermal nerve fiber density (IENFD), but a wide adaptation of the technique is limited by complexity and time requirement. 8,9 We recently reported that a simple epidermal skin-prick application of histamine could reliably induce an axon-reflex flare response on the foot in people with and without type 1 diabetes mellitus (T1DM) and neuropathic complications.…”
Section: Introductionmentioning
confidence: 99%